Beispiel Nr: 03
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 9x -2y =5\\ 5x -2y = 1 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} I \qquad 9 x -2 y =5\\ II \qquad 5 x -2 y = 1 \\ \text{I nach x auflösen}\\ 9 x -2 y =5 \\ 9 x -2 y =5 \qquad /+2 y\\ 9 x =5 +2 y \qquad /:9 \\ x =\frac{5}{9} +\frac{2}{9} y \\ \text{I in II}\\ 5 (\frac{5}{9} +\frac{2}{9} y ) + -2 y = 1 \\ 2\frac{7}{9} +1\frac{1}{9} y -2 y = 1 \qquad / -2\frac{7}{9} \\ +1\frac{1}{9} y -2 y = 1 -2\frac{7}{9} \\ -\frac{8}{9} y = -1\frac{7}{9} \qquad /:\left(-\frac{8}{9}\right) \\ y = \frac{-1\frac{7}{9}}{-\frac{8}{9}} \\ y=2 \\ x =\frac{5}{9} +\frac{2}{9} y \\ x =\frac{5}{9} +\frac{2}{9} \cdot 2 \\ x=1 \\ L=\{1/2\} \end{array} & \begin{array}{l} I \qquad 9 x -2 y =5\\ II \qquad 5 x -2 y = 1 \\ \text{I nach y auflösen}\\ 9 x -2 y =5 \\ 9 x -2 y =5 \qquad /-9 x\\ -2 y =5 -9x \qquad /:\left(-2\right) \\ y =-2\frac{1}{2} +4\frac{1}{2}x \\ \text{I in II}\\ 5x + -2(-2\frac{1}{2} +4\frac{1}{2} x ) = 1 \\ 5 -9 x -2 x = 1 \qquad / -5 \\ -9 x -2 x = 1 -5 \\ -4 x = -4 \qquad /:\left(-4\right) \\ x = \frac{-4}{-4} \\ x=1 \\ y =-2\frac{1}{2} +4\frac{1}{2} x \\ y =-2\frac{1}{2} +4\frac{1}{2} \cdot 1 \\ y=2 \\ L=\{1/2\} \end{array} \end{array} $